2021
DOI: 10.52547/jfl.9.37.205
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Intercultural Movie Clips on EFL Learners’ Social and Cultural Identity in Virtual Communities of Practice

Abstract: The relationship between identity and language learning has attracted the scholars` attention in the fields of second language acquisition (SLA) with considerable focus on social and cultural dimensions of language learning. However, relatively little research has been devoted to examining the identity construction of language learners in virtual communities of practice despite the global trend of foreign language instruction. Consequently, the current mixed methods classroom-based study investigated whether t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…Participants expressed a higher level of awareness (Metacognitive CQ) of how cultural background influences the interactions with people from different cultures ( t =17.94, p <0.001). These results confirm the findings of recent research in this direction ( Truong and Tran, 2014 ; Cao and Meng, 2020 ; Nematzadeh et al, 2021 ). Many studies that have used films in pedagogical interventions have rather focused on improving language skills, but in addition to the main purpose, higher cultural awareness ( Peng and Wu, 2016 ; Chaya and Inpin, 2020 ) and a higher level of tolerance for ambiguity and differences have often been achieved ( Genç, 2018 ).…”
Section: Discussionsupporting
confidence: 92%
“…Participants expressed a higher level of awareness (Metacognitive CQ) of how cultural background influences the interactions with people from different cultures ( t =17.94, p <0.001). These results confirm the findings of recent research in this direction ( Truong and Tran, 2014 ; Cao and Meng, 2020 ; Nematzadeh et al, 2021 ). Many studies that have used films in pedagogical interventions have rather focused on improving language skills, but in addition to the main purpose, higher cultural awareness ( Peng and Wu, 2016 ; Chaya and Inpin, 2020 ) and a higher level of tolerance for ambiguity and differences have often been achieved ( Genç, 2018 ).…”
Section: Discussionsupporting
confidence: 92%
“…That is, being knowledgeable in both cultures enables them to improve their ICC. In this sense, as indicated in this study, it can be concluded that movies can be regarded as one of the most influential tools to promote foreign language teaching and enhance ICC (Chaya & Inpin, 2020; Gu & Zhao, 2021; Nematzadeh, Haddad, & Tajadini, 2021). Champoux (1999) also agrees that a movie as a useful learning tool can be used in different ways in the classroom.…”
Section: Introductionmentioning
confidence: 59%